Beta 2-integrin LFA-1 signaling through phospholipase C-gamma 1 activation. - Kanner, S B (1993)
One of the beta 2-integrins found on hematopoietic cells is lymphocyte function-associated antigen 1 (LFA-1), a lymphocyte/myeloid cell-specific receptor that binds to members of the intercellular adhesion molecule (ICAM) family on antigen-presenting cells. Stimulation of LFA-1 with antibodies or purified ICAMs induces augmentation of T-cell antigen receptor (TCR)-directed T-cell responsiveness. In the present study, LFA-1 was shown to be linked to the tyrosine kinase signaling pathway that stimulates tyrosine phosphorylation and activation of phospholipase C-gamma 1 (PLC-gamma 1). Integrin beta-chain (CD18) crosslinking independently induced downstream mobilization of intracellular Ca2+ and potently costimulated TCR-induced Ca2+ flux with an increase in both amplitude and kinetics. beta 2-Integrin signaling through this pathway was completely inhibited by herbimycin A and was prevented by TCR modulation. Coligation of the TCR via antibody and LFA-1 with a counter-receptor in the form of a soluble ICAM-1/Rg fusion protein resulted in prolonged tyrosine phosphorylation of PLC-gamma 1. Monoclonal antibodies to both the alpha chain (CD11a) and the beta chain (CD18) of LFA-1 induced Ca2+ mobilization to different levels, suggesting epitope specificity for activation potential. In addition to PLC-gamma 1, tyrosine phosphorylation of an 80-kDa protein substrate was augmented following CD18 crosslinking but was not TCR-dependent. The beta 2-integrin LFA-1 on T cells is therefore directly linked to a tyrosine kinase pathway that stimulates signaling by phosphatidylinositol-specific PLC-gamma 1.